Legal Responsibility of Clinicians Ethical Dilemma and Approach of Physicians From Various Specialties in Child Abuse Cases - Çelik, Gonca Gül; Meral, Demet; Tahiroğlu, Ayşegül Yolga; Çekin, Necmi; Avcı, Ayşe (The Bulletin of Legal Medicine, 2007)
Child and adolescent psychiatrists not only treat patients for sexual abuse but also largely contribute to legal procedures. This fact utterly brings a need for better clarification of the controversial ethical dilemma which addresses patient confidentiality versus the legal responsibility of clinicians. The aims of this study were to determine how this issue was addressed by physicians from various specialties and to uncover unmet needs that needed to be brought to discussion. A questionnaire was prepared including data about a mock abuse case for which legal procedure was imminent. Participants were asked if they would start a legal procedure for the given case. The participating physicians were child and adolescent psychiatrists and forensic medicine specialists who volunteered to complete the questionnaire. There were a total of 106 participants; 72 of them were forensic medicine specialists and 34 of them were child and adolescent psychiatrists. 94 (88.7%) of participants reported that they would start legal procedure, while 12 (11.3%) of them reported that they would not. 13.9% of forensic medicine specialists and 5.9% of child and adolescent psychiatrists reported that they would not start legal procedure. The ethical and legal responsibilities of clinicians were discussed in the scope of this case. Key words: Sexual abuse, false allegation, responsibility of clinicians, ethical dilemma